2022
DOI: 10.25126/jtiik.2022925422
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor yang Berpengaruh pada Adopsi E-Commerce dan Dampaknya Bagi Kinerja UKM di Kabupaten Subang

Abstract: <p>Teknologi yang semakin berkembang dan maju di sektor bisnis telah membuat pelaku Usaha Kecil dan Mengengah melakukan inovasi pelayanan yang berkaitan dengan penggunaan teknologi <em>e-commerce</em>. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh faktor teknologi, organisasi, lingkungan terhadap adopsi <em>e-commerce</em> dan kinerja serta menganalisis pengaruh adopsi <em>e-commerce</em> terhadap kinerja UKM. Objek penelitian ini adalah UKM yang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 9 publications
1
31
0
3
Order By: Relevance
“…This facilitates individuals in comprehending market trends, consumer behaviour, and their business performance, all of which hold significance in making wellinformed decisions. In order for students to effectively market and sell their products or services online, it is imperative that they possess a thorough comprehension of the optimal utilisation of e-commerce platforms (Ausat et al, 2022;Yusuf et al, 2022). It is imperative for individuals to possess the requisite knowledge and skills to proficiently administer e-commerce platforms, efficiently oversee inventory management, streamline the payment process, and deliver a gratifying purchasing experience to clients.…”
Section: Discussionmentioning
confidence: 99%
“…This facilitates individuals in comprehending market trends, consumer behaviour, and their business performance, all of which hold significance in making wellinformed decisions. In order for students to effectively market and sell their products or services online, it is imperative that they possess a thorough comprehension of the optimal utilisation of e-commerce platforms (Ausat et al, 2022;Yusuf et al, 2022). It is imperative for individuals to possess the requisite knowledge and skills to proficiently administer e-commerce platforms, efficiently oversee inventory management, streamline the payment process, and deliver a gratifying purchasing experience to clients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also found that using technology during a pandemic can improve business performance [5]. Because of the availability of services in the form of technology, consumers can access and place orders from a variety of locations, and all services desired by consumers can be delivered immediately [6]. As a result, the business world will be able to provide the best service possible.…”
Section: Introductionmentioning
confidence: 99%
“…Information technology has advanced and evolved in response to societal demands. Every industry, but especially commercial enterprise, is benefiting from the expansion and improvement of information technology [1]. Because of this, corporate actors are under constant pressure to develop novel information technology-based services in order to gain widespread acceptance, particularly in commercial exchanges [2].…”
Section: Introductionmentioning
confidence: 99%